HUBUNGAN KEMOTERAPI DAN ASUPAN ENERGI DENGAN STATUS GIZI PASIEN KANKER NASOFARING DI RSUP FATMAWATI JAKARTA PADA TAHUN 2019 - Annisa Dyah Chairini (2020)
Nasopharyngeal carcinoma cases in Indonesia, especially in men, ranks 4th. One of the problems that can arise in nasopharyngeal cancer patients is nutritional problems that can be influenced by the side effects of chemotherapy and energy intake in cancer patients. Energy and nutrients deficiency are common problems in nasopharyngeal cancer patients, which could increase the mortality and morbidity of the patients. The purpose of this study was to determine the relationship between chemotherapy and energy intake on the nutritional status of nasopharyngeal cancer patients at Fatmawati General Hospital in 2019. This research method uses cross-sectional study design and the type of analytic descriptive research is observational. The number of samples in this study was 33 patients taken based on consecutive sampling techniques. Research data were collected using medical record sheets and direct body mass index measurements to obtain the nutritional status, medical record sheets to obtain the chemotherapy status, and Food Recall 24 hour sheets to obtain energy intake. Data were analyzed by the Chi-Square test showed there was no relationship between chemotherapy on the nutritional status of nasopharyngeal cancer patients (p=0,270) and there was a relationship between the energy intake on nutritional status of nasopharyngeal cancer patients (p=0.015). The conclusion, there was a relationship between the energy intake on the nutritional status of nasopharyngeal cancer patients, while chemotherapy did not have a relationship to the nutritional status of nasopharyngeal cancer patients